2019
DOI: 10.23910/ijbsm/2019.10.6.2041a
|View full text |Cite
|
Sign up to set email alerts
|

Walking and Dry Season Stresses Modulates the Physiological, Heamatological and Biochemical Profiles of Indigenous Local Goats in Andaman and Nicobar Islands

Abstract: A study was designed to assess the walking stress and dry seasonal effect on physiological, heamatological and biochemical profiles in indigenous local goat breeds of Andaman and Nicobar Islands (ANI). Twelve bucks of adult age of 3 to 4 yr of age with good body condition (score 5-6) were selected and divided into two groups, viz. group-I: control (n=6, not exposed to stress) and group-II: treatment (n=6, exposed to walking and dry season stress). In treatment group, animals were walked upto10 km to and fro fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The results pertaining to certain hematological indices of goats in this study support recent studies using different goat breeds with different experimental designs. A significant positive correlation obtained between Hb and RBC (r = 0.805) and PCV (r = 0.424) in goats (89); between Hb and HCT (r = 0.57) for beef (90); and between MCV and MCH (r = 0.95) Perumal et al (91) and Karki et al (87) findings reported that RBC was negatively correlated with MCV (r = −0.58) and MCH (r = −0.71) in the kiko goat breed. In contrast, the results of this investigation differ from those of the other studies.…”
Section: Correlation Coe Cients Between Homatological Indicesmentioning
confidence: 99%
“…The results pertaining to certain hematological indices of goats in this study support recent studies using different goat breeds with different experimental designs. A significant positive correlation obtained between Hb and RBC (r = 0.805) and PCV (r = 0.424) in goats (89); between Hb and HCT (r = 0.57) for beef (90); and between MCV and MCH (r = 0.95) Perumal et al (91) and Karki et al (87) findings reported that RBC was negatively correlated with MCV (r = −0.58) and MCH (r = −0.71) in the kiko goat breed. In contrast, the results of this investigation differ from those of the other studies.…”
Section: Correlation Coe Cients Between Homatological Indicesmentioning
confidence: 99%
“…Moreover, it is fundamental to take into consideration the factors which could influence the hematological profile of a patient. In particular, it is now well known that the hematological parameters in goats undergo changes concerning many factors such as breed [23,29,30], age [22,31], sex [23,32], physiological/reproductive status [33][34][35], season [36][37][38], environmental and management factors [39][40][41], nutrition [42], and diseases [43][44][45][46]. Based on these differences, it is necessary to establish for every breed appropriate physiological reference intervals that could be used to evaluate the physiological or pathological status of the animal.…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress causes multiple diseases in ruminants (Ayemele et al 2021, Huang et al 2021. Thus recognizing their importance, antioxidant profiles were studied in various conditions such as in pregnancy (Nawito et al 2016), postpartum periods (Tanvi et al 2017, different rearing systems (Karthik et al 2021) and in various season stresses (Kumar et al 2019, Perumal et al 2019. The present study aimed to evaluate the influence of variations of the rearing system, breed and fecundity of indigenous goats of Andaman by estimating the level of antioxidant markers, viz.…”
mentioning
confidence: 96%
“…Andaman and Nicobar Islands (ANI) has mainly two breeds of goat, viz. Andaman local goat (ALG) and Teressa goat, which are reared for meat purpose (Perumal et al 2019). It is a unique island where goats are the primary livestock species and are considered as an insurance source during disaster periods similar to the mainland region (Regar et al 2020).…”
mentioning
confidence: 99%